Tripod Position and Pursed Lip Breathing on Respiration Rate in COPD Patients - Lutfi Wahyuni; Catur Prasastia Lukita Dewi (STIKes Patria Husada Blitar, 2023)
Many people with COPD develop emphysema and chronic bronchitis. Both conditions cause obstruction of airflow in the respiratory system and cause an increase in the frequency of external respiration. One of the non-pharmacological management is tripod position and pursed lip breathing. This study aimed to determine the effect of giving a tripod position and pursed lip breathing on respiration rate in COPD patients. The design of this study used a one group pretest-post test design. The population in this study were all COPD patients at Bangil Hospital, Pasuruan in June 2021. The sampling technique of this study was consecutive sampling, the sample was obtained by 25 respondents. The instrument used observation and SOP. The results showed that the average respiration rate before giving the combination of tripod position and pursed lip breathing was 28.8x/minute, and the average value of respiration rate after giving the tripod position and pursed lip breathing was 23.2x/minute. Wilcoxon test results value = 0.000 on respiration rate before and after the combination of tripod position and pursed lip breathing, which means that tripod position and pursed lip breathing are proven to be effective on respiration rate in COPD patients. Tripod position and pursed lip breathing will loosen the chest cavity, provide positive pressure on the lungs so that air can go in and out more smoothly and reduce shortness of breath